Infiltração de água em neossolos regolíticos do rebordo do planalto do Rio Grande do Sul - Stürmer, Sidinei Leandro Klöckner (2008)
Neossolos Regolíticos (Regosols/Entisols), even is being successfully used from an economical perspective with horticulture and reforestation, are fragile from a natural resource perspective because their small depth, presence of stones and/or rocks, near surface lithic contact, fractures in saprolite and frequent occurrence in steep slopes. Neossolos have been classified as materials of low potential use, which in part caused inadequate morphological field description by soil survey teams. Population growth and urban expansion requires over areas with Neossolos require larger volume of data and a more specific analysis for a better interpretation of these soils capacity to filtrate water, retain and transform solute and water contributing to the maintenance of the water quality that reaches the underground reservoirs. In that sense this study was an attempt to generate information on Neossolos from the edge of the Plateau of Rio Grande do Sul State. Five Neossolos profiles were studied regarding their chemical (pH, soil organic carbon, bases and aluminum saturation, cations exchange capacity); physical (aggregation, bulk density of soil and saprolite, pore space, size distribution of soil particles, water storage capacity of the saprolite, fractures in the saprolite) and morphologic (profile thickness, soil color, consistence) analyses were performed. A correlation analysis of these attributes with the water infiltration in soil resulted that there were great variations in the hidraulic behavior among the Neossolos sampled in different location as well as among the replications in the same location. The main components analysis indicated that the soil water infiltration has strong relationship with the total porosity, angles of fractures in the saprolite and with the distribution of the particle size fractions of the soil.